New species and new records of chigger mites (Acariformes, Trombiculidae) from Cambodia - Antonovskaia, Anastasia A.; Morand, Serge; Stekolnikov, Alexandr A. (Zootaxa, 2024)
Two new chigger species, Leptotrombidium mondulkiri sp. nov. and Walchia keoseima sp. nov., and one new subspecies, Leptotrombidium pilosum cambodiensis subsp. nov., are described from Cambodia. Three species, Walchia lupella (Traub and Evans, 1957), W. micropelta (Traub and Evans, 1957), and W. kritochaeta (Traub and Evans, 1957), are for the first time reported from the country. A redescription of W. lupella is given based on new materials from Cambodia and Thailand.